Mitigating false blocking problem in wireless ad hoc networks - Chong, W.K. (Springer New York LLC, 2018)
The traditional IEEE802.11 Request-to-Send/Clear-to-Send (RTS/CTS) handshaking in medium access control layer has been widely adopted in wireless ad hoc networks to reduce the hidden node problem. However, it induces the false blocking problem, which occurs when nodes are prevented from replying to any incoming RTS packets when they are in deferring state after overhearing the RTS and/or CTS packets. Worse still, these unreplied RTS packets will then cause other neighbouring nodes to defer blindly which propagates the false blocking problem, resulting in exhaustion of scarce energy resource and throughput degradation. In this paper, we propose an adaptive Ready-to-Send and blocking notification (RSBN) scheme to mitigate the false blocking problem. The adaptive RSBN scheme not only validates the overheard RTS packets to avoid blind deferment but also informs neighbouring nodes of the nodesâ deferring status to block unnecessary RTS packets. We validate the proposed scheme by simulations and the results have shown that the adaptive RSBN scheme can achieve higher performance. Â© 2017, Springer Science+Business Media New York.